The effects of banana ripeness on quality indices for puree production - Yap, M.; Fernando, W.; Brennan, C.; Jayasena, Vijay; Coorey, R. (Elsevier, 2017)
The physical and chemical compositional changes of Cavendish bananas were investigated according to the ripening stages determined by peel colour as classified in the Banana Ripening Guide. There is a need for the utilization of second grade bananas that are deemed unsuitable for retail sale, but are still appropriate for human consumption, for the long term sustainability of the banana industry. The optimum stage of ripeness of banana for puree making for food product development was determined through comparisons of the physical, chemical and sensory qualities. Banana pulp samples were analysed for texture, total soluble solids, starch, sugar, total ash, and potassium and magnesium contents at different ripening stages. At stage 5 ripeness, banana pulp had potassium (584 mg/100 g), magnesium (58 mg/100 g), total sugar (5.2 g/100 g) and starch (1.8 g/100 g) contents. Stage 5 ripened bananas were found to be the most suitable for puree production. Sensory acceptability results showed that the puree produced with second grade test bananas was rated significantly better compared to a commercial puree.